Transportation as a Driver for Sustainable Tourism in Terengganu, Malaysia - Yusoff, Siti Zanariah; Ghazali, Mohd Faradi; Mohamad, Nazilah; Hassan, Isyaku; Abdullah, Nor Hafizah; Azmy, Sharipah Nur Mursalina Syed; Azmi, Nor Jijidiana (The journal of contemporary issues in business and government, 2021)
This study aims to examine the effectiveness of transportation sector in Terengganu, Malaysia. The study employed a qualitative approach in which interviews and document analysis were used. The data were analysed using inductive thematic analysis. The findings show that the majority of informants are satisfied with the transportation sector around the main focus areas at Kuala Terengganu, but suggest increased public transport in interesting places located far from the city. However, the analysis shows that the main weaknesses that need to be addressed are the telecommunications systems in the tourist areas. The lack of internet access limits alternatives in choosing affordable transportation for tourists. The findings of this study contribute significantly to the enrichment of the literature in tourism and transportation. It also has positive implications for helping tourism operators such as government and private agencies involved to strengthen the tourism sector in Terengganu.